2007
DOI: 10.1590/s0103-65132007000100012
|View full text |Cite
|
Sign up to set email alerts
|

Análise da confiabilidade humana via redes Bayesianas: uma aplicação à manutenção de linhas de transmissão

Abstract: A análise de confiabilidade humana (ACH) estuda a execução das ações humanas em um determinado sistema, considerando suas limitações e os fatores que influenciam no seu desempenho. A literatura apresenta os modelos de ACH de primeira e segunda geração. Esses modelos apresentam algumas deficiências. Dentre elas, destacam-se suposições irreais de independência e simples representação binária de eventos. Diante disso, apresentam uma grande dificuldade na modelagem das ações humanas. Este artigo mostra que modelar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…In Brazil it has been observed that the human reliability is still in an embryonic step once only two article in Brazilian journal were identified [10,11]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil it has been observed that the human reliability is still in an embryonic step once only two article in Brazilian journal were identified [10,11]…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach was conducted in the Scielo database, in which are some of the major national periodicals. Search with the keywords "human reliability" in both English and Portuguese has resulted in only 2 articles by [10,11], both published in the journal production. The term "reliability" found 111 articles.…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…The methodology Bayesian belief networks (BBN) provides a greater flexibility as not it only allows for a more realistic representation of the dynamic nature of man-system, but also allows for representation of the relationship of dependence among the events and performance shaping factors [10].…”
Section: Bayesian Network Methodsmentioning
confidence: 99%
“…For example, [Martins et al, 2013] proposed a study on the application of Bayesian networks to the human reliability analysis (HRA) of an oil tanker operation focusing on collision accidents. This study uses a four-phase methodology (familiarization, qualitative analysis, quantitative analysis, incorporation) to accomplish HRA [Swain et al, 1983] using the integration of fault trees and Bayesian networks [Droguett et al, 2007]. Also, to specify the reliability for new product development, [Murthy et al, 2009] developed a new model of product life cycle in which the life cycle was divided into eight phases and grouped into three stages (Predevelopment, Development, Post-development).…”
Section: Reliability Designmentioning
confidence: 99%